2017
DOI: 10.1093/mnras/stx2563
|View full text |Cite
|
Sign up to set email alerts
|

Quasar outflows at z ≥ 6: the impact on the host galaxies

Abstract: We investigate quasar outflows at z 6 by performing zoom-in cosmological hydrodynamical simulations. By employing the SPH code GADGET-3, we zoom in the 2R 200 region around a 2×1012 M ⊙ halo at z = 6, inside a (500 Mpc) 3 comoving volume. We compare the results of our AGN runs with a control simulation in which only stellar/SN feedback is considered. Seeding 10 5 M ⊙ BHs at the centers of 10 9 M ⊙ halos, we find the following results. BHs accrete gas at the Eddington rate over z = 9 − 6. At z = 6, our most-mas… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
89
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 68 publications
(105 citation statements)
references
References 152 publications
16
89
0
Order By: Relevance
“…6 and 7 in Valiante et al) to derive f gas estimates, and reported in the figure the ratios between these values and the f MS gas (M star , z). Finally, depleted gas reservoirs in z ∼ 6 galaxies experiencing AGN feedback are also found in the hydrodynamical simulations by Barai et al (2018), with f gas ∼ 20 − 30% lower with respect to the prelude of the feedback phase (private communication).…”
Section: Low Gas Fractions In Dusty Agnmentioning
confidence: 63%
“…6 and 7 in Valiante et al) to derive f gas estimates, and reported in the figure the ratios between these values and the f MS gas (M star , z). Finally, depleted gas reservoirs in z ∼ 6 galaxies experiencing AGN feedback are also found in the hydrodynamical simulations by Barai et al (2018), with f gas ∼ 20 − 30% lower with respect to the prelude of the feedback phase (private communication).…”
Section: Low Gas Fractions In Dusty Agnmentioning
confidence: 63%
“…Hydrodynamical simulations of z 6 > Barai et al (2017) suggest that negative feedback may drive quasars above the local scaling SMBH-galaxy relations. Barai et al (2017) argue that conical, symmetric outflows can remove gas efficiently from galactic disks while still allowing gas to accrete onto the SMBH perpendicular to the biconical outflow. Furthermore, the same simulations without quasar feedback tend to grow their stellar mass ahead of the SMBH, driving galaxies below the local correlations.…”
Section: Discussionmentioning
confidence: 99%
“…AGN accretion disks are thought to drive energetic winds (Murray et al 1995) and/or relativistic jets that suppress star formation (Hopkins & Elvis 2010;Zubovas & King 2014;Costa et al 2015), thereby impacting galactic structure and evolution. This is one of the leading theoretical (Di Matteo et al 2005;Faucher-Giguère et al 2012;Barai et al 2017;Anglés-Alcázar et al 2017) pictures used to explain correlations between SMBH masses and galactic stellar masses (Magorrian et al 1998;Ferrarese & Merritt 2000;Gebhardt et al 2000;Kormendy & Ho 2013) and the luminosity function of local massive galaxies (Benson et al 2003). The sphere of influence of SMBHs, inside which their gravity dominates that of the stars, gas, and dark matter, range from a few 10 s to 100 pc, while the local scaling relations of M M bulge BH -apply on stellar bulge scales, i.e., several kpc.…”
Section: Introductionmentioning
confidence: 97%
“…Recently, a study by Barai et al (2018) using zoom-in hydrodynamical simulations to determine the effect of outflows on the host galaxy and surrounding environment of quasars at z ≥ 6, has demonstrated that outflows could indeed be a dominant feature of high redshift quasars. Even though the quasar host galaxies at z ∼ 6 are accreting significant amounts of cosmic gas, AGN feedback succeeds in reducing the inflow by ∼ 12%, with ∼ 20% of the quasar outflows having speeds greater than the escape velocity of 500 km s −1 , subsequently succeeding in ejecting gas out of the host galaxy, and regulating the on-going star formation (Barai et al 2018).…”
Section: Should We Expect To See Outflows In All High-z Quasars?mentioning
confidence: 99%